Contribuição ao processo de dimensionamento de cortinas atirantadas - Figueiredo, Juliana Gonzalez (2018)
One of the main issues of the analysis of anchored retaining walls is the role of the anchors on the stability. Two situations should be verified according to the first edition of the Brazilian Standard NB-565: the so-called external and internal failures. In the first case the anchors did not participate in the failure mechanism, and the Brazilian method (developed by Nunes and Velloso), based on the Culmann method, was used in the analysis. The anchor load was calculated from the critical slip surface, and the fixed length was positioned from the slip surface corresponding to an acceptable safety factor, e.g. 1.5. The same approach is suggested by the NBR-5629 standard. The internal failure, analysed by the Ranke and Ostermayer method, considered the anchors in the failure mechanism in order to calculate the free length of the anchor. The anchor load was obtained from earth pressure theories. Computer programs using Slice Methods predominate nowadays. In those cases the anchor loads are considered in two ways: contributing to the moment equilibrium and increasing the stresses at the base of the slices, still an issue in the latter case. The present research analyses the design of anchored retaining walls, based on usual dimensions and typical soil properties of gneissic residual soil. A comparison between the Brazilian, the Ranke Ostermayer, the simplified Bishop´s methods – in this case using a commercial software – is undertaken. The finite element method is used as a reference for the analyses carried out.